Characterizing the scent and chemical composition of Panthera leo marking fluid using solid-phase microextraction and multidimensional gas chromatography–mass spectrometry-olfactometry - Simone B. Soso (Nature Portfolio, 2017)
Abstract Lions (Panthera leo) use chemical signaling to indicate health, reproductive status, and territorial ownership. To date, no study has reported on both scent and composition of marking fluid (MF) from P. leo. The objectives of this study were to: 1) develop a novel method for simultaneous chemical and scent identification of lion MF in its totality (urine + MF), 2) identify characteristic odorants responsible for the overall scent of MF as perceived by human panelists, and 3) compare the existing library of known odorous compounds characterized as eliciting behaviors in animals in order to understand potential functionality in lion behavior. Solid-phase microextraction and simultaneous chemical-sensory analyses with multidimensional gas-chromatography-mass spectrometry-olfactometry improved separating, isolating, and identifying mixed (MF, urine) compounds versus solvent-based extraction and chemical analyses. 2,5-Dimethylpyrazine, 4-methylphenol, and 3-methylcyclopentanone were isolated and identified as the compounds responsible for the characteristic odor of lion MF. Twenty-eight volatile organic compounds (VOCs) emitted from MF were identified, adding a new list of compounds previously unidentified in lion urine. New chemicals were identified in nine compound groups: ketones, aldehydes, amines, alcohols, aromatics, sulfur-containing compounds, phenyls, phenols, and volatile fatty acids. Twenty-three VOCs are known semiochemicals that are implicated in attraction, reproduction, and alarm-signaling behaviors in other species.